LA COMPRÉHENSION DE LA RELATION TEXTE – MUSIQUE DANS LADY MACBETH DU DISTRICT DE MTSENSK DE DMITRI CHOSTAKOVITCH - TOMA, Valentina (Studia Universitatis Babes-Bolyai Musica, 2013)
The Understanding of the Text-Music Relationship in Lady Macbeth of the Mtsensk District by Dmitry Shostakovich. This study proposes an analysis of the opera Lady Macbeth of Mzensk by Dmitry Shostakovitch from the point of view of the relationship between text and music. The approach is coordinated according to the hermeneutic law, which implies that the whole must be understood by the particular, and the particular by the whole, this rule which comes from the ancient rhetoric, being transferred (after Hans-Georg Gadamer) by the mediation of the hermeneutic of the art of declamation towards the art of comprehension. Thus, the hermeneutic research implies also elements of rhetoric, one of these elements being pars pro toto, based on the principle of “unity between selection and combination in the formation of the basic image: as a part which will represent the whole (…)” Knowing all this, we have insisted only on a limited number of musical examples extracted from the original score, which are relevant from the point of view of the relationship between text and music. “Words in the opera cannot be dissociated from music, but when one looks with his eyes at the text in the score and does not here it with his ears, lots of things may look distasteful.” This passage quoted from a letter of Dmitry Shostakovitch expresses his esthetics and the principle which lies at the basis of the opera Lady Macbeth of Mzensk.